Dynamics of Nahdlatul Wathan Islamic Education - Tahir, Tarmizi; Ansori, M. Afif; Andari, An An (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to examine the struggle of Nahdlatul Wathan to participate in and make a major contribution to the Indonesian nation's progress. The research is written based on literary studies and in-depth understanding and accumulated understanding from various trusted primary book sources. This type of research is qualitative with a library research approach. Data collection techniques are carried out by data collection. Sources of data come from books and journals. Data analysis technique using Content Analysis. Results of this study show that Nahdlatul Wathan Diniyah Islamiyah Islamic education's existence in terms of education meaning has undergone evolution/development as a continuum of meaning when history first occurred, present, and future. The historical phenomenon shows that apart from establishing a men's Islamic education (Nahdlatul Wathan), figures (founders) also founded a women's Islamic education (Nahdlatul Banat). Nahdlatul Wathan is a social organization engaged in fields of education, social, and Islamic da'wah and adheres to Islam ahlusunnah wal jama'ah. The Imam Syafi'i school continues to exist in this Pancasila. This shows that Nahdlatul Wathan, as an Islamic organization, has always fought for ahlusunnah wal jama'ah to uphold the creed so that it can be accepted by Muslims in this country.